Peningkatan literasi keuangan masyarakat desa Sebangar melalui edukasi dan pendampingan keuangan keluarga - Yona Fitri; Elbina Mamla Saidah (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aims to improve the financial literacy level of the people of Sebangar Village, Bathin Solapan District, Bengkalis Regency, Riau Province. The community’s low understanding of personal and family financial management often leads to consumptive behavior, unproductive debt, and an inability to manage household income effectively. Therefore, this program is designed to foster awareness and develop basic skills in managing finances independently and sustainably. The activities were carried out using a service-learning approach based on community participation. The methods included household financial management training, budgeting simulation, practical exercises in preparing family financial plans, and mentoring on saving strategies adapted to the local economic context. Evaluation was conducted through pre-test and post-test to measure participants’ improvement in financial literacy concepts. The results showed a significant increase in participants’ understanding and skills in financial management. Based on the evaluation, 85% of participants experienced an improvement in financial literacy scores from low to moderate and high categories. In addition, participants were able to create more structured monthly expenditure plans, record household cash flow, and begin to practice regular saving habits. This education and mentoring program on family financial management has proven effective in enhancing the financial literacy and behavior of Sebangar Village residents. It has implications for strengthening family economic independence and can serve as a model for community empowerment programs based on financial education in other rural areas.